2020
DOI: 10.1073/pnas.1909110117
|View full text |Cite
|
Sign up to set email alerts
|

NK cells clear α-synuclein and the depletion of NK cells exacerbates synuclein pathology in a mouse model of α-synucleinopathy

Abstract: The pathological hallmark of synucleinopathies, including Lewy body dementia and Parkinson’s disease (PD), is the presence of Lewy bodies, which are primarily composed of intracellular inclusions of misfolded α-synuclein (α-syn) among other proteins. α-Syn is found in extracellular biological fluids in PD patients and has been implicated in modulating immune responses in the central nervous system (CNS) and the periphery. Natural killer (NK) cells are innate effector lymphocytes that are present in the CNS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 75 publications
2
128
0
Order By: Relevance
“…That particular preclinical model utilized α-syn transgenic mice that over-express human α-syn with the A53T mutation, and combined it with an injection of human α-syn PFFs into the dorsal striatum. The depletion of NK cells in this model of α-syn-induced pathology suggests that NK cells can contribute to the clearance of α-syn aggregates, or prevent their formation [75]. The mice we used in our study also have deficiencies in NK cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…That particular preclinical model utilized α-syn transgenic mice that over-express human α-syn with the A53T mutation, and combined it with an injection of human α-syn PFFs into the dorsal striatum. The depletion of NK cells in this model of α-syn-induced pathology suggests that NK cells can contribute to the clearance of α-syn aggregates, or prevent their formation [75]. The mice we used in our study also have deficiencies in NK cells.…”
Section: Discussionmentioning
confidence: 94%
“…They are implicated in diseases of autoimmunity and within the CNS, and can interact with microglia [74]. Recently, it was reported that systemic depletion of NK cells in a preclinical model of PD exacerbated α-syn pathology [75]. That particular preclinical model utilized α-syn transgenic mice that over-express human α-syn with the A53T mutation, and combined it with an injection of human α-syn PFFs into the dorsal striatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that striatal injection of a-Syn PFFs but not monomers in WT mice can trigger neuroinflammation by increasing peripheral immune cells infiltration in the CNS (Earls et al, 2019). Apparently, this immune reaction would precede the dopaminergic neurodegeneration (Harms et al, 2017) but, it cannot be excluded that the magnitude and the efficacy of the immune reaction can also modulate the spread of the pathology observed as it was recently suggested by (Earls et al, 2020).…”
Section: Propagation Of Alpha-synuclein: Evidence and Considerationsmentioning
confidence: 96%
“…Therefore, immunomodulatory-based approaches aimed at halting the propagation and burden of extracellular α-syn, and in turn diminishing the inflammatory response, are currently being tested as a therapeutic for PD and related synucleinopathies (reviewed in 23 ). Recently, it was discovered that natural killer (NK) cells efficiently internalize and degrade α-syn aggregates via the endosomal/lysosomal pathway, a novel and highly relevant function of NK cells in synucleinopathies 24 . The number of circulating NK cells in PD patients is increased compared to non-PD controls 25 .…”
Section: Introductionmentioning
confidence: 99%